ПІДВИЩЕННЯ ЕФЕКТИВНОСТІ АЛГОРИТМІВ ПОБУДОВИ МАКРОМОДЕЛЕЙ ОБ'ЄКТІВ ЕЛЕКТРОЕНЕРГЕТИЧНИХ СИСТЕМ - Стахів, П.Г.; Козак, Ю.Я.; Гоголюк, О.П. (Інститут електродинаміки НАН України, Київ, 2014)
In the paper the problems to create discrete macromodels of electric power system objects on the basis of real time characteristics obtained with the help of modern systems of monitoring systems is considered. The procedure of creation of such macromodels using the "black box" conception in the form of discrete state equations with the help of expert analysis and separation of variables is described. References 3.